Social Interaction and Class Struggles in Noughts & Crosses by Malorie Blackman - Rahmawati, Aulia Nur; Saktiningrum, Nur (Universitas Gadjah Mada, 2024)
This research employs a sociological approach to literature, drawing on Georg Simmel's social interaction theory and Karl Marx's class struggle concepts, to analyze the dynamics between the upper-class Crosses and the lower-class Noughts in the novel Noughts & Crosses. The study identifies five forms and six types of social interactions, encompassing superordination and subordination, exchange, conflict, prostitution, and sociability, along with character-based classifications such as the miser, the spendthrift, the stranger, the adventurer, the nobility, and the poor. The central focus lies in understanding the struggles of the Noughts in their pursuit of social equality within a deeply divided society. Despite collective and individual efforts, fueled by class consciousness and the formation of the Liberation Militia, the research concludes that achieving equality remains elusive. The powerful Crosses, driven by hidden manipulations and a desire to maintain the existing system, thwart the Noughts' endeavors, underscoring the persistent challenges faced by the lower class in a society marked by reverse racism.